Analisis Perbedaan Beban Kerja Tiap Shift pada Operator SPBU COCO dan DODO yang Beroperasi 24 Jam di Daerah Istimewa Yogyakarta - Ratna; Surya Andika Sjalamuddin (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2019)
This The study aims to determine the difference in workload of operator officers in terms of morning, afternoon and night work shifts between COCO’s (Corcoated Owned Corporated Operated). and DODO’s (Dealer Owned Operated Dealers) Gas Stations that operate 24 hours in Yogyakarta Special Region. There are differences between the morning, afternoon and night shifts complained of by the operator, namely that the afternoon shift tends to be more crowded than the other two shifts so that operators feel more tired while working in the afternoon shift. There are differences between the two types of gas stations, namely the ownership system, physical facilities, and management management systems. This study was conducted to analyze the workload both physical and mental in each shift and then evaluate the current shift work system. The measurement of physical workload was carried out objectively by measuring the operator's heart rate to be converted into oxygen consumption and Heart Rate Range (HRR), the results of these measurements were then analyzed statistically using the ANOVA test and the post-hoc Least Significance Different (LSD) test. ) Mental workloads were measured using subjective methods with the NASA-TLX questionnaire. The conclusion obtained is that there are differences in the physical workload of operators in each shift at COCO and DODO gas stations. The operator's oxygen consumption value in each shift is classified as mild to moderate, while the HRR value is still below the recommended limits or can be said to be safe. The mental workload of operators at COCO and DODO gas stations tends to be high to very high categories and indicators of physical needs are indicators.